Sharia Principles in the Financial Services Authority Regulation on Dispute Settlement Alternatives - Ro'fah Setyowati; Bagya Agung Prabowo (Faculty of Law, Sriwijaya University, Indonesia, 2021)
There is a legal disharmony with the Sharia Banking Law in the regulation on alternative dispute resolution institutions. This problem arises because the regulation does not pay attention to sharia principles, as mandated by Article 55, Paragraph 3 of the Sharia Banking Law. Meanwhile, the application of sharia principles is a spiritual right of consumers which also requires legal protection. This research is intended to assess alternative dispute resolution institutions' regulations, particularly Financial Services Authority Regulation from a consumer protection perspective, particularly spiritual rights. This research is categorized as an empirical normative study, using a philosophical, historical approach and a content analysis of the Financial Services Authority Regulation. The results of this study indicate that the Financial Services Authority Regulation on Alternative Dispute Resolution Institutions has not accommodated spiritual rights in dispute resolution for the Islamic banking industry. A weak understanding of spiritual rights causes it in the context of dispute resolution. It also creates another problem in the form of a lack of attention and policies that support the protection of spiritual rights, both in regulatory and banking institutions. In the context of dispute resolution, there are general consumer rights, such as the right to get advocacy, while the application of sharia principles is a special right. Based on these findings, it is recommended that regulatory institutions, particularly the Financial Services Authority, pay adequate attention to the entire financial service industry under their respective characteristics. It is an important matter because the protection of spiritual rights supports the development of the Islamic finance industry both in Indonesia and globally.